2005
DOI: 10.1103/physrevlett.95.125002
|View full text |Cite
|
Sign up to set email alerts
|

Stability of an Impulsively Accelerated Density Interface in Magnetohydrodynamics

Abstract: In the framework of ideal incompressible magnetohydrodynamics, we examine the stability of an impulsively accelerated, sinusoidally perturbed density interface in the presence of a magnetic field that is parallel to the acceleration. This is accomplished by analytically solving the linearized initial value problem, which is a model for the Richtmyer-Meshkov instability. We find that the initial growth rate of the interface is unaffected by the presence of a magnetic field, but for a finite magnetic field the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
78
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 9 publications
6
78
0
Order By: Relevance
“…This interaction is mediated by sound waves. Besides compressibility, other interesting physical phenomena, for example shocks propagating into viscous fluids (Miller & Ahrens 1991), the influence of elastic/plastic properties of solid materials Piriz et al 2008) and the effect of magnetic fields on the dynamics of corrugated shocks in plasmas (Wheatley et al 2005), are certainly worth studying. In fact, when dealing with more complex properties and states of matter, as well as the inclusion of magnetic fields for shocks propagating in plasmas, the interaction between the shock fronts and boundaries may be sustained not only by the longitudinal adiabatic sonic waves, but with another family of wave fronts that propagate at speeds other than the speed of sound in ordinary gases.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction is mediated by sound waves. Besides compressibility, other interesting physical phenomena, for example shocks propagating into viscous fluids (Miller & Ahrens 1991), the influence of elastic/plastic properties of solid materials Piriz et al 2008) and the effect of magnetic fields on the dynamics of corrugated shocks in plasmas (Wheatley et al 2005), are certainly worth studying. In fact, when dealing with more complex properties and states of matter, as well as the inclusion of magnetic fields for shocks propagating in plasmas, the interaction between the shock fronts and boundaries may be sustained not only by the longitudinal adiabatic sonic waves, but with another family of wave fronts that propagate at speeds other than the speed of sound in ordinary gases.…”
Section: Introductionmentioning
confidence: 99%
“…We will appeal to such an interpretation in discussing results from our numerical simulations. Recently, Samtaney [5] has shown that the RM instability is suppressed by the presence of a magnetic field, which was also confirmed analytically by Wheatley et al [6]. The magneto-hydrodynamics (MHD) RM instability includes nonlinear MHD waves such as a slow-mode shock [5,7].…”
Section: Introductionmentioning
confidence: 57%
“…The amplitude of the oscillations are larger for stronger incident shocks as expected. In Figure 1(d) the amplitude of the density interface for each shock strength are plotted and for comparison the saturation amplitudes predicted by the incompressible theory of Wheatley et al [6] are shown as horizontal lines. Predictably, the numerical simulations agree well with the incompressible theory at low Mach numbers, with the differences growing with increasing Mach number.…”
Section: Single Density Interfacementioning
confidence: 99%
“…This was further reconfirmed by analytical incompressible Magnetohydrodynamics (MHD) theory of an impulsively accelerated interface developed by Wheatley et al [7,8,9]. In Samtaney's work, the magnetic field was aligned to the motion of the shock, the suppression of the RMI was caused by the bifurcation of the vortex sheet which transported the baroclinically generated vorticity away from the contact discontinuity by a pair of MHD shocks.…”
Section: Introductionmentioning
confidence: 67%